Photoconversion‐Tunable Fluorophore Vesicles for Wavelength‐Dependent Photoinduced Cancer Therapy. Issue 19 (15th March 2017) - He, Hui; Ji, Shuangshuang; He, Yang; Zhu, Aijun; Zou, Yelin; Deng, Yibin; Ke, Hengte; Yang, Hong; Zhao, Youliang; Guo, Zhengqing; Chen, Huabing
Abstract : Photoconversion tunability of fluorophore dye is of great interest in cancer nanomedicine such as fluorescence imaging, photodynamic therapy (PDT), and photothermal therapy (PTT). Herein, this paper reports wavelength‐dependent photoconversional polymeric vesicles of boron dipyrromethene (Bodipy) fluorophore for either PDT under 660 nm irradiation or PTT under 785 nm irradiation. After being assembled within polymeric vesicles at a high drug loading, Bodipy molecules aggregate in the conformations of both J ‐type and H ‐type, thereby causing red‐shifted absorption into near‐infrared region, ultralow radiative transition, and ideal resistance to photobleaching. Such vesicles further possess enhanced blood circulation, preferable tumor accumulation, as well as superior cell uptake as compared to free Bodipy. In particular, the vesicles mainly generate abundant intracellular singlet oxygen for PDT treatment under 660 nm irradiation, while they primarily produce a potent hyperthermia for PTT with tumor ablation through singlet oxygen‐synergized photothermal necrosis under 785 nm irradiation. This approach provides a facile and general strategy to tune photoconversion characteristics of fluorophore dyes for wavelength‐dependent photoinduced cancer therapy. Abstract : Photoconversion‐tunable Bodipy polymeric vesicles for wavelength‐dependent photoinduced cancer therapy are demonstrated, which mainly generate abundant intracellular singlet oxygen for photodynamic therapy treatment under 660 nm irradiation, while primarily producing potent hyperthermia for photothermal therapy with tumor ablation through singlet oxygen‐synergized photothermal necrosis under 785 nm irradiation.